Lack of consensus in ALS genetic testing practices and divergent views between ALS clinicians and patients. Issue 3 (3rd April 2019) - Klepek, Holly; Nagaraja, Haikady; Goutman, Stephen A.; Quick, Adam; Kolb, Stephen J.; Roggenbuck, Jennifer
Abstract: Recent advances in ALS gene discovery have both empowered and challenged clinicians providing evaluation and care for persons with ALS, many of whom seek an answer as to the cause of their condition. In order to study clinician practices and attitudes towards genetic testing, we surveyed members of the Northeast ALS Consortium, an international group of specialist ALS clinicians; responses were received from 80 of 255 (response rate = 31.4%). While 92.3% indicated they offered genetic testing to patients with familial ALS, 57.0% offered testing to patients with ALS and a family history of dementia, and 36.9% offered testing to patients with sporadic ALS, revealing a lack of consensus with respect to the approach to the typical ALS patient encountered in clinical practice. In addition, comparison of clinician and patient attitudes towards genetic testing revealed that clinicians valued the scientific potential of testing, but were less likely to say they would have testing themselves, or to see the value in testing for family members. People with ALS were more likely to see value of testing for themselves and for family members, and less likely to strongly value the scientific potential of testing.